Penerapan Logika Fuzzy Guna Menggali Minat dan Bakat Calon Mahasiswa dalam Bidang Komputer - Mahendra, Agung; Kristian, Billy; Serliyawati, Ellicia; Aprizal, Yarza; Mahmud, Mahmud; Veronica, Maria (Universitas Multi Data Palembang, 2024)
This research aims to implement fuzzy logic for recommending the interests and potential talents of students planning to major in computer science. The outcome of this research is a web-based application called prodipilihanku, which displays one of the Computer Science Study Programs based on the interests and talents of prospective students within the scope of the Computer Science Study Program in South Sumatra, especially Palembang. The results indicate that the interest and talent assessment application, developed using the Tsukamoto Fuzzy Logic method, is capable of suggesting study programs in the field of computer science for users based on their responses to the questionnaire. The outcomes of this interest and aptitude test can be considered by users when registering for a computer science study program. If the calculations within the application align with the results of the summation in Tsukamoto's fuzzy logic, the prodipilahnku can be utilized.